2017
DOI: 10.5539/ijb.v9n3p78
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Characterization of Fruits and Morphoanatomy of the Mesocarp of Acrocomia Species (Arecaceae)

Abstract: The genus Acrocomia (Arecaceae) is widely distributed in the Neotropics, without consensus on the number of species. The arboreal species are explored in their native countries. To subsidize better use of the observed variation in fruits of different species for product extraction, taxonomy, conservation and genetic improvement, our objective was to characterize biometrically the fruits and anatomically the mesocarp from natural populations of A. aculeata, A. intumescens and A. totai. We observed different col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 14 publications
(18 reference statements)
5
31
0
Order By: Relevance
“…There was a significant difference for fruit weight, epicarp and endocarp contents (wet basis -WB), pulp moisture, pulp oil content (dry and wet basis) and pulp oil yield and total oil yield/fruit (WB) (p<0.05). The fruit weight varied from 29 to 38 g (fresh weight), which is consistent with the average result (39 g) reported by Vianna et al (2017) and in the range of 24 to 58 g observed for 35 genotypes by Conceição et al (2015b). The fruits showed epicarp and endocarp contents varying from 15 to 24% and 28 to 35% (WB), respectively, and both comprised around half of the fruit weight.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…There was a significant difference for fruit weight, epicarp and endocarp contents (wet basis -WB), pulp moisture, pulp oil content (dry and wet basis) and pulp oil yield and total oil yield/fruit (WB) (p<0.05). The fruit weight varied from 29 to 38 g (fresh weight), which is consistent with the average result (39 g) reported by Vianna et al (2017) and in the range of 24 to 58 g observed for 35 genotypes by Conceição et al (2015b). The fruits showed epicarp and endocarp contents varying from 15 to 24% and 28 to 35% (WB), respectively, and both comprised around half of the fruit weight.…”
Section: Resultssupporting
confidence: 89%
“…The potencial of macauba as an oil source has been evaluated focusing on biodiesel production (BERGMANN et al, 2013;COLOMBO et al, 2018;CONCEIÇÃO et al, ,a, b, 2015bFERRARI and AZEVEDO FILHO, 2012;LOPES and STEIDLE NETO, 2011). Therefore the oil content and the fatty acid profile of both the mesocarp and kernel oils and fruit characteristics have been more studied than its nutritional value (CONCEIÇÃO et al, ,a,b, 2015bHIANE et al, 2005;VIANNA et al, 2017). Information related to nutritional composition is scarce, and a large variation has been observed for the protein content of the mesocarp ranging from 1.5 to 6.7% (RAMOS et al, 2008;COIMBRA and JORGE, 2011), while total dietary fiber has been presented for some macauba genotypes without evaluating the sugar content.…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomic distinction of the species has been demonstrated based on morphological data and geographic distribution [4], leaf anatomy [1], and fruit biometry [68]. However, A. totai is commonly regarded as A. aculeata due to the pronounced morphological similarity of both species, and because both have fruits with similar biometric and color characteristics [68]. Our results were congruent with the current taxonomic classification of the species.…”
Section: A Aculeatasupporting
confidence: 87%
“…It has been documented in eastern Bolivia, Paraguay, Central-west Brazil to northern Argentina [4,15]. The taxonomic distinction of the species has been demonstrated based on morphological data and geographic distribution [4], leaf anatomy [1], and fruit biometry [68]. However, A. totai is commonly regarded as A. aculeata due to the pronounced morphological similarity of both species, and because both have fruits with similar biometric and color characteristics [68].…”
Section: A Aculeatamentioning
confidence: 99%
“…(Cargnin et al, 2008;César et al, 2015;Ciconini et al, 2013;Pires et al, 2013). Given the good prospects for its genetic improvement and domestication, current production is expected to rise above 6500 kg oil•ha -1 •yr -1 , provided that in recent studies the figures for extracted oil have already exceeded this amount for scenarios of 400 plants•ha -1 , surpassing even African oil palm in terms of liters of biodiesel•ha -1 (Colombo et al, 2017;Luis and Scherwinski-Pereira, 2017;Vianna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%